Konsep Putusan Hakim pada Pengadilan Agama di Indonesia - Kahar Muzakir (Lembaga Pengembangan Kinerja Dosen, 2025)
A ruling is a decision delivered by a judge in a trial, aimed at resolving a dispute or legal matter between the parties involved. There are various types of rulings, such as Declarative Rulings, Constitutive Rulings, Condemnatory Rulings, Contradictory Rulings, and Default Rulings. Each ruling has two kinds of authority: binding authority and executive authority, which refers to the power to enforce the ruling. Judges play a central role and have a significant responsibility in upholding the law and justice. Therefore, judges' professionalism must continually be improved to ensure that rulings are fair and in accordance with applicable regulations. Not only judges, but all members and staff of the Religious Courts are also required to enhance their professionalism in performing their duties. This is particularly important considering the expanded jurisdiction of Religious Courts in handling cases in the field of Islamic economics, which is still relatively new. As a result, the application of the concept of judicial rulings in Indonesia’s Religious Courts must continue to evolve to meet the public's expectations for justice based on the law.